Pengaruh Inovasi Kualitas Pelayanan terhadap Loyalitas Konsumen melalui Mediasi Kepuasan Konsumen pada Bisnis Ritel - Achmad Satrio; Wahju Wulandari; Mulyono Mulyono (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study examines the role of service innovation in fostering customer loyalty, with customer satisfaction acting as a mediating variable, in the context of PT Pos Indonesia (Persero) KCP Lawang. The research is driven by the growing competition in the courier service industry and the observed decline in the company’s customer satisfaction index. Employing a quantitative approach with an explanatory research design, data were collected from 100 respondents using an accidental sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS 4 software. nThe results reveal that service innovation exerts a significant positive effect on customer satisfaction, indicating that innovative service features, improved processes, and responsiveness to customer needs can substantially enhance the overall customer experience. Furthermore, customer satisfaction was found to significantly and positively influence customer loyalty, demonstrating its importance in retaining customers in a competitive market. Interestingly, the direct effect of service innovation on customer loyalty was not statistically significant, suggesting that innovation alone is insufficient to guarantee customer loyalty without first addressing satisfaction. The mediation analysis confirms that customer satisfaction serves as a full mediator between service innovation and loyalty, meaning that the benefits of innovation in services are fully realized through their ability to meet and exceed customer expectations. These findings underscore the strategic importance of prioritizing customer satisfaction initiatives in the development of service innovations. For PT Pos Indonesia and similar service providers, focusing on tailoring innovative offerings to customer preferences and needs can enhance satisfaction levels, which in turn fosters long-term loyalty. The study contributes to the literature by clarifying the indirect pathway through which service innovation influences loyalty and offers practical implications for designing customer-centered innovation strategies in the courier service sector.